The Implementation of Pedagogical Strategies in Inclusive Education Program for Pupils with Special Needs among Mainstream Teachers: A Case study - Maarof, Mazmi; Jalaluddin, Noor Syahira (Jurnal Pendidikan Bitara UPSI, 2019)
Inclusive Education Program for pupils with Special Needs is the current national agenda that is being solidified in the Malaysia Education Blueprint 2013-2025 and supported by Zero Reject Policy beginning January 2019. Adhering to the current development, Inclusive Education Program for pupils with Special Needs has been restructured and implemented with improvement in training for all teachers so that the acceptance of Special Needs pupils in mainstream classes could be realised through meaningful teaching and learning practice and to increase competencies the abilties of all pupils. Addressing this need, a qualitative study in the form of case study has been conducted to analyse the teaching stretegies implemented by mainstream teachers teaching in the Inclusive Education Program focussing on the process of teaching phase evaluated in Le Francois model of teaching. The participants consisted of three mainstream teachers teaching in a primary school in Melaka whom were evaluated through interview as the instrument for this study. Themes and sub-themes were analysed qualitatively. The study shown that to a certain extent respondents implemented the pedagogical strategies that aligned with inclusive pedagogy in their teaching phase and made necessary efforts to provide condusive teaching context for special needs and mainstream pupils who were involved in the Inclusive Education Programme.